Cobrança pelo uso dos recursos hídricos no Rio São Francisco - Praes, Elaine Oliveira (2014)
This paper is about the charged and collected water use by charging, one of the main National Water Resources Policy´s instruments for managing, which was established by Law No. 9,433 of January 8, 1997. The charge use of water resources arose from actions aimed to conserve this natural resource, which is due to water multiple uses and the growing demand. As water has become increasingly scarce, the concern about its availability on the planet is urgent. The charge for water use is a key tool in the management of water resources, as well as being used for rationing this resource, promoting the balance between supply and demand, generating financial donations to fund programs and projects that promote the improvement water management resources and their conservation. In this study the data were analyzed and collected from water charging resources used in São Francisco River between 2010 and 2013 collected by the states that are part of the watershed in question was identified by the use sector and the irrigated areas in the State of Sergipe located in Baixo São Francisco region. Regarding the methodology it was applied to obtain the descriptive, exploratory and explanatory results, with data collection obtained through bibliographic, documentary and case study research. The results of this study showed that the water charging by use is significant, compared to the estimated value, but the total amount collected is not significant, considering the needs of environmental recovery of the basin; the values invested in the basin of São Francisco River is still modest, considering the interest and importance of the development of the basin, both promoting social and economic development and for the conservation of the basin. It is concluded that charging for water use is an essential management tool and has promoted actions for rational use and conservation of this natural resource. However, there is still a long way to achieve its objectives. A route to be built with the management of decentralized actions, with the participation of those concerned in this subject and especially with making investments to improve the management of water resources, ensuring the conservation and quality improving of this natural resource